Design of Savonius Vertical Axis Wind Turbine for Vehicle - Arbiyani, Filian; Lasut, Fernando Pranata (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
The use of cellular phones is increasing in society, but due to the limited battery capacity of cell phones, it is necessary to charge the battery when travelling in the long distances. The Savonius type wind turbine has a potential as an energy source harvesting the wind energy flowing around the car. However, due to the available space on the car, careful design of Savonius vertical axis wind turbine for vehicle is necessary. The research is conducted numerically using MATLAB software. The wind speed, Reynolds number, and electric power output are numerically simulated to obtain the swept area design. Innovative PLA material in the design is also investigated by simulating the effect of mass inertia moment to the design. This design of Savonius vertical axis wind turbine for vehicle is expected to charge maximum four cell phone batteries with the total electrical output of 60 W. The optimum swept area design of Savonius vertical axis wind turbine for vehicle is 0.150 m2 using 3 fins, PLA filament material, with an overlap of 5.3 cm, and a diameter for each blade 22 cm according to the overlap ratio used of 0.242. This Savonius vertical axis wind turbine design is feasible as an energy source for vehicle owing to its compact design, innovative material used in the design, and providing the electric power demand in the vehicle.